1989
DOI: 10.1093/bja/63.6.661
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Atracurium and Laudanosine in the Elderly

Abstract: The pharmacokinetics of a bolus dose of atracurium 0.6 mg kg-1 and its metabolite laudanosine were studied in 11 elderly (mean age 80.9 yr) and 10 young patients (mean age 23.8 yr) undergoing elective surgery. The elimination half-life (T1/2 beta) of atracurium was significantly longer in the elderly group (23.1 v. 20.1 min), but there was no significant difference between the two groups in clearance (Cl), the volume of distribution (V beta) or the mean residence time (MRT) of atracurium. Laudanosine T1/2 beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 17 publications
(32 reference statements)
4
25
3
Order By: Relevance
“…Elimination of atracurium occurs in both tissue and plasma, making traditional I-compartment pharmacokinetic models inaccurate. Therefore, the area under the plasma concentration-time curve (AUC) was used to calculate pharmacokinetic variables (Fahey et al 1984;Kent et al 1989;Ward et al 1983) or 2-compartment models were modified to account for different elimination rate constants from the central and peripheral compartments (Fisher et al 1986Kitts et al 1990).…”
Section: Atracuriummentioning
confidence: 99%
See 2 more Smart Citations
“…Elimination of atracurium occurs in both tissue and plasma, making traditional I-compartment pharmacokinetic models inaccurate. Therefore, the area under the plasma concentration-time curve (AUC) was used to calculate pharmacokinetic variables (Fahey et al 1984;Kent et al 1989;Ward et al 1983) or 2-compartment models were modified to account for different elimination rate constants from the central and peripheral compartments (Fisher et al 1986Kitts et al 1990).…”
Section: Atracuriummentioning
confidence: 99%
“…Since these age-related changes occur simultaneously, neither the t' l2/3 nor the recovery from the neuromuscular blockade alters with age ). In the elderly, however, the t' l2/3 may be longer and the V d larger (Kent et al 1989;Kitts et al 1990) than in young adults, which could prolong recovery from neuromuscular blockade in the elderly, particularly after multiple or large doses. Thermal injury (Maratke et al 1989) did not alter atracurium pharmacokinetics but caused significant resistance to the neuromuscular effects of this compound, reflected by a 3-to 4-fold increase in the concentration of the drug required to produce a given degree of twitch depression.…”
Section: Atracuriummentioning
confidence: 99%
See 1 more Smart Citation
“…The highest kinetic (1.9) and dynamic (1.4) ratios among infants and children were used to calculate the composite factor. Kent et al (1989) studied the pharmacokinetics of a bolus dose of atracurium 0.6 mg/kg in 11 elderly patients (80.9 + 8.2 years) and compared the results to those in 10 young adults (23.8 + 4.3 years) ( Table 3). The ratios of kinetic parameters between the two groups were 1.3 to 1.6.…”
Section: Intermediate-acting Nmba Atracuriummentioning
confidence: 99%
“…To help resolve this question, several groups of investigators have reported on the time course of the plasma concentrations oflaudanosine after the administration of a single intravenous bolus injection of atracurium (Fahey et al 1985;Kent et al 1989;Vandenbrom et al 1990;Ward et al 1987). Immediately after administration of atracurium (2 min), the concentrations oflaudanosine were highest and decreased during the next 8 to 10 min.…”
mentioning
confidence: 99%